Greenland ice core evidence of the 79 AD Vesuvius eruption - C. Barbante (Climate of the Past, 2013)
Volcanic tephra are independent age horizons and can synchronize strata of various paleoclimate records including ice and sediment cores. The Holocene section of the Greenland Ice Core Project (GRIP) ice core is dated by multi-parameter annual layer counting, and contains peaks in acidity, SO42− and microparticle concentrations at a depth of 429.1 to 429.3 m, which have not previously been definitively ascribed to a volcanic eruption. Here, we identify tephra particles and determine that volcanic shards extracted from a depth of 429.3 m in the GRIP ice core are likely due to the 79 AD Vesuvius eruption. The chemical composition of the tephra particles is consistent with the K-phonolitic composition of the Vesuvius juvenile ejecta and differs from the chemical composition of other major eruptions (≥ VEI 4) between 50–100 AD.